(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
While a considerable body of literature advocates for participatory evaluation methodologies within community-centred community-campus engagement (CCE) projects, there has been limited study to date on how a “community-first”, or community-driven approach to CCE may be informed and strengthened by reflexive evaluation practices. Reflexive evaluation involves a critical reflection on the positionality of participants in relation to the processes they are engaged in and attempting to influence. In response to this gap, this article develops a reflexive account of our activities and influence, as academics, within an evaluation of the first phase of the multi-year pan- Canadian CCE project known as Community First: Impacts of Community Engagement (CFICE). Building on the experiences of community and academic partners across a collective reflective evaluation of over forty demonstration projects within Phase I of CFICE, we reflexively examine our own efforts to incorporate common community-first CCE working practices into the evaluation processes to which we contributed. This examination reinforces scholarly assertions about the crucial position of community voices in co-governance of CCE projects, the need to reduce institutional constraints to community participation, and the value of nourishing relationships within CCE work. The approach explored in this article complements more general evaluation methods for practitioners seeking to ensure accountability to community-first values in their work. The article also explores how reflexive evaluation can inform practitioners about deeper personal and collective introspection and transformations related to relationships and processes associated with employing community-first CCE working practices.